Determination of natural bowing angle for standing and sitting for Malaysian population - 428277 Hamidah Abidin; Mat Rebi Abdul Rani; Fakulti Kejuruteraan Mekanikal (2007)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal - Industri)) - Universiti Teknologi Malaysia, 2007